1968
DOI: 10.1128/aem.16.9.1326-1330.1968
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli on Plants

Abstract: The distribution, enumeration, and identification of lactobacilli on vegetable plants were studied in an area described geographically as being subtropical and moist. The lactobacilli were obtained, by means of quantitative enrichment procedures in Rogosa's SL broth, from 35.3% of all samples incubated at 32 C, and from 15.4%, of the samples incubated at 45 C. Less than 10 lactobacilli/g of plant material were enumerated in 54% of all positive samples. The lactobacilli were found much less frequently and in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 7 publications
1
26
1
Order By: Relevance
“…Plants harbor a numerous and varied microflora. Although the numbers of lactic acid bacteria on plant materials are highly variable, most investigations have shown that their number is very low, often in the range of 10-1000 cells per g [12][13][14][15][16][17], which represents approx. 0.01-1.0% of the total microbial population.…”
Section: Lactic Acid Bacteria-plant Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants harbor a numerous and varied microflora. Although the numbers of lactic acid bacteria on plant materials are highly variable, most investigations have shown that their number is very low, often in the range of 10-1000 cells per g [12][13][14][15][16][17], which represents approx. 0.01-1.0% of the total microbial population.…”
Section: Lactic Acid Bacteria-plant Relationshipmentioning
confidence: 99%
“…Besides the increase in total number, the distribution among different types of microorganisms changes. The dominating, aerobic, Gram-negative bacteria are replaced by facultative and anaerobic, Gram-positive bacteria of the genera Leuconostoc, Lactobacillus, Pediococcus, Bacillus, and Clostridiurn [15][16][17]21,22]. However, in lactic acid fermentation of plants like alfalfa, ryegrass, cucumbers, carrots, and red beets, it has been shown that Gram-negative bacteria of the family Enterobacteriaceae can be present in high numbers and cause problems such as excessive gas in cucumbers [23] and pectinolytic softening in carrots and beets [12].…”
Section: Lactic Acid Bacteria-plant Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Mundt and Hammer (1968) reported that they isolated the following lactobacilli from okra plants: L. plantarum, L. fermenti and L. casei. The species of the genus Lactobacillus that were isolated from okra fruits were not identical to the identified strains of okra plants.…”
Section: Resultsmentioning
confidence: 99%
“…Lactobacillus brevis and Lactobacillus plantarum are responsible for the natural fermentation of many vegetables, although L. plantarum is by far the predominant species in most fermentations (Etchells et al, 1975). Mundt and Hammer (1968) studied the distribution of lactobacilli on okra plants. No attempt to study the microflora during fermentation of okra fruits is reported.…”
Section: Introductionmentioning
confidence: 99%